2005
DOI: 10.1002/ajmg.a.30920
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular studies on two further families with Simpson‐Golabi‐Behmel syndrome

Abstract: The Simpson-Golabi-Behmel syndrome (SGBS) (OMIM 312870) is an overgrowth/multiple congenital anomalies syndrome caused by a semi-dominant X-linked gene encoding glypican 3 (GPC3). It shows great clinical variability, ranging from mild forms in carrier females to lethal forms with failure to thrive in males. The most consistent findings in SGBS are pre- and postnatal macrosomia, characteristic facial anomalies and abnormalities affecting the internal organs, skeleton, and on some occasions, mental retardation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Pilia et al [1996] first described causative mutations in glypican‐3 ( GPC3 ). Several later publications have confirmed these findings [Hughes‐Benzie et al, 1996; Lindsay et al, 1997; Veugelers et al, 1998, 2000; Lin et al, 1999; Xuan et al, 1999; Li et al, 2001; Mariani et al, 2003; Rodriguez‐Criado et al, 2005; Romanelli et al, 2007; Sakazume et al, 2007]. However, in several families there have been no identifiable mutations, and the detection rate for GPC3 mutations and deletions in individuals with SGBS ranges widely from 37% (7/19) [Li et al, 2001] to 70%; 7/10 in the study of Veugelers et al [2000] and 26/37 in the study of Lin et al [1999].…”
Section: To the Editormentioning
confidence: 74%
“…Pilia et al [1996] first described causative mutations in glypican‐3 ( GPC3 ). Several later publications have confirmed these findings [Hughes‐Benzie et al, 1996; Lindsay et al, 1997; Veugelers et al, 1998, 2000; Lin et al, 1999; Xuan et al, 1999; Li et al, 2001; Mariani et al, 2003; Rodriguez‐Criado et al, 2005; Romanelli et al, 2007; Sakazume et al, 2007]. However, in several families there have been no identifiable mutations, and the detection rate for GPC3 mutations and deletions in individuals with SGBS ranges widely from 37% (7/19) [Li et al, 2001] to 70%; 7/10 in the study of Veugelers et al [2000] and 26/37 in the study of Lin et al [1999].…”
Section: To the Editormentioning
confidence: 74%
“…The risk of developing an embryonal tumor was evaluated by Lapunzina [] at 10% in view of the previous reports but including cases with no GPC3 mutation [Lapunzina et al, ]. Among the 63 reviewed cases, three had developed Wilms tumor, three hepatoblastomas and one medulloblastoma [Hughes‐Benzie et al, ; Lindsay et al, ; Li et al, ; Rodríguez‐Criado et al, ; Thomas et al, ], whereas we had only one case of Wilms tumor in our series. This leads to an overall frequency of 8%, but the small size of the sample hampers evaluation of a precise frequency.…”
Section: Discussionmentioning
confidence: 93%
“…Although we could not collect information for all clinical features in all cases and were thus unable to evaluate the precise frequency of rare associations, our study improves significantly the knowledge on SGBS. Our data may be compared with those of the 63 cases carrying a mutation in GPC3 for whom clinical details are available in the literature [Hughes‐Benzie et al, ; Lindsay et al, ; Veugelers et al, ; Okamoto et al, ; Li et al, ; Mariani et al, ; Day and Fryer, ; Rodríguez‐Criado et al, ; Young et al, ; Romanelli et al, ; Sakazume et al, ; Glamuzina et al, ; Gertsch et al, ; Gurrieri et al, ; Yano et al, ; Garavelli et al, ; Thomas et al, ; Li and McDonald, ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been shown that SGBS patients have an increased risk during childhood of embryonic cancers such as nephroblastoma, hepatoblastoma, neuroblastoma, or gonadoblastoma. However, the long-term effects of the SGBS syndrome remain uncertain since there have been very few reports concerning the natural history of this syndrome in adulthood [Neri et al, 1998;Rodríguez-Criado et al, 2005].…”
Section: Molecular Studymentioning
confidence: 99%